2017
DOI: 10.1186/s12875-017-0633-1
|View full text |Cite
|
Sign up to set email alerts
|

Patient and care characteristics of self-referrals treated by the general practitioner cooperative at emergency-care-access-points in the Netherlands

Abstract: BackgroundIn the Netherlands, out-of-hours primary care is provided in general practitioner-cooperatives (GPCs). These are increasingly located on site and in collaboration with emergency departments of hospitals (ED). At such sites, also called emergency-care-access-points (ECAP), the GPC is generally responsible for the triage and treatment of self-referrals who used to attend the ED. To evaluate the effects and safety of this novel organisation, we studied the characteristics and the quality of care given b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 22 publications
1
28
0
1
Order By: Relevance
“…We did not look at patients who received no diagnostic imaging and where injuries could have been missed. Nevertheless, previous studies showed that the treatment of patients at the GPC maintained the safety and quality of care, and missed injuries were equal at the ED and GPC . The observational design has the risk of not recognizing factors outside the ECAP that might have contributed to the results.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…We did not look at patients who received no diagnostic imaging and where injuries could have been missed. Nevertheless, previous studies showed that the treatment of patients at the GPC maintained the safety and quality of care, and missed injuries were equal at the ED and GPC . The observational design has the risk of not recognizing factors outside the ECAP that might have contributed to the results.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, multiple studies have shown the opposite. Implementations of ECAPs resulted in fewer X‐ray examinations, also when this was available for GPCs . Furthermore, there was no difference in risk assessment and indications for X‐ray requests between access and no access to radiology for GPCs …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As concerns primary care physicians' accessibility in modern healthcare world, several authors have advocated the efficiency of primary health-care facilities located near EDs to alleviate ED attendance with patients in need of primary care. This method has been experienced in some location in Belgium and Europe with hopeful and reliable results [6,9,12,16,[24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%